1994
DOI: 10.1002/jbm.820280113
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of implanted collagen material during bone induction

Abstract: Studies were made on the fate of implanted material during bone induction. Mixtures of 1 mg of crude bone morphogenetic protein (BMP), or bovine serum albumin as a control, and 1.5 mg of bovine collagen, were pressed into discs and implanted under the fascia of the rectus abdominus muscle of rats. The tissues with implants were fixed 7, 10, and 14 days later and examined histologically. On day 7 after implantation, the implant was surrounded and invaded by alkaline phosphatase-positive cells. New bone and cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Bone defects and regeneration are important clinical considerations in oral and maxillofacial and reconstructive surgery occur in a wide variety of clinical situations, and successful closure of these defects remains as a major concern in the early phase of bone healing as which organization of the clot is completed can be followed clinically, whereas bone remodeling can be determined biochemistry via ALP or radiographically. (13,14) The ALP level express an early sign of osteoblast secretion of matrix which subsequently determined to become osteiod. This activity never been isolated from connective tissue away from bone thus indicated that its source is limited to existing bone.…”
Section: Discussionmentioning
confidence: 99%
“…Bone defects and regeneration are important clinical considerations in oral and maxillofacial and reconstructive surgery occur in a wide variety of clinical situations, and successful closure of these defects remains as a major concern in the early phase of bone healing as which organization of the clot is completed can be followed clinically, whereas bone remodeling can be determined biochemistry via ALP or radiographically. (13,14) The ALP level express an early sign of osteoblast secretion of matrix which subsequently determined to become osteiod. This activity never been isolated from connective tissue away from bone thus indicated that its source is limited to existing bone.…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment similar to ours. Horisaka et al5 used bovine collagen in combination with bovine bone morphogenetic proteins (BMP) to study osteogenesis. They found that the collagen/BMP implant rapidly induced calcification and new bone formation when placed in rat muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In biomaterial science, collagen is used for sutures, soft‐tissue augmentation, and as a skin substitute 4. Collagen combined with bone morphogenetic proteins (BMP) and implanted into host tissue has an affinity for connective tissue and will gradually degrade and resynthesize to form new bone 5. Blumenthal3 reported his composite DFDBA/collagen graft material to be highly hemostatic, able to expand to fill defects, and well retained when placed into bony lesions of the jaw and maxilla of humans and baboons.…”
Section: Introductionmentioning
confidence: 99%
“…O termo refere-se ao processo pelo qual as células tronco mesenquimais, presentes no tecido circunjacente ao local do enxerto, são induzidas à diferenciação em células de linhagem osteogênica (ALEXANDER, 1987). Esse mecanismo está relacionado à atividade da "bone morphogenetic protein" (BMP) (URIST, 1965;BESSHO et al, 1992;YABU et al, 1992;OGAWA et al, 1992;BESSHO & IZUKA, 1994;HORISAKA et al, 1994) presente na matriz óssea. Todavia, a preservação dessa proteína e de sua atividade osteoindutora em fragmentos ósseos conservados em glicerina é motivo de dúvida.…”
Section: Introductionunclassified